(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article examines the practical aspects of interaction between the Federal Tax Service of Russia (FTS) and the Federal Financial Monitoring Service (Rosfinmonitoring) in the field of countering the legalization of income from tax crimes. The exchange of information between departments is analyzed, the most significant information flows are identified. The key areas for improving interdepartmental cooperation are highlighted: improving the quality of analytical tools, optimizing data exchange, introducing modern information processing technologies and clearly regulating the legal framework for cooperation. The proposed measures are aimed at enhancing the effectiveness of joint work, responsiveness to identified threats and strengthening the resilience of the national financial system to criminal practices.